2014
DOI: 10.1155/2014/371570
|View full text |Cite
|
Sign up to set email alerts
|

Absence of HPV Infection Is Associated with Smoker Patients with Squamous Cell Carcinoma of the Oropharynx

Abstract: The purpose of this study was to evaluate the survival of patients with SCC of the oropharynx, according to the presence of HPV and tobacco consumption. A total of 37 patients were followed up for at least 5 years after being diagnosed with SCC of the oropharynx. The biopsy tissue was submitted to the polymerase chain reaction (PCR) and in situ hybridization (ISH) methods for broad determination of HPV presence, to identify the presence of high-risk viruses (16 and 18). 12 of the 37 (32.4%) samples were HPV po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…21 Similarly Soares et al also observed that in HPVnegative cases, the level of tobacco consumption was significantly higher. 19 Our results are compatible with previous reports, showing that in Brazil, the main causes of tonsillar carcinomas are alcohol and tobacco. 13,24 It has been suggested that NK tonsillar carcinoma originates from the reticular crypt epithelium, presenting higher susceptibility for HPV infection.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…21 Similarly Soares et al also observed that in HPVnegative cases, the level of tobacco consumption was significantly higher. 19 Our results are compatible with previous reports, showing that in Brazil, the main causes of tonsillar carcinomas are alcohol and tobacco. 13,24 It has been suggested that NK tonsillar carcinoma originates from the reticular crypt epithelium, presenting higher susceptibility for HPV infection.…”
Section: Discussionsupporting
confidence: 93%
“…[13][14][15] The association of known risk factors, such as tobacco and alcohol, with oropharyngeal SCC has been found to be minimal in HPV-positive cases, whereas higher levels of consumption were reported in HPV-negative patients. 19,20 The aim of this study was to determine the presence of HPV in tonsillar SCC in patients from Guatemala and Brazil.…”
Section: Statement Of Clinical Relevancementioning
confidence: 99%